The Salmonella Typhimurium Effector SpvB Subverts Host Membrane Trafficking by Targeting Clathrin and AP-1 - Yuan, Yi; Wang, Xinghao; Jin, Jie; Tang, Zhiheng; Xian, Wei; Zhang, Xinyi; Fu, Jiaqi; He, Kangmin; Liu, Xiaoyun (Molecular & cellular proteomics, 2023)
Salmonella enterica, the etiological agent of gastrointestinal and systemic diseases, translocates a plethora of virulence factors through its type III secretion systems to host cells during infection. Among them, SpvB has been reported to harbor an ADP-ribosyltransferase domain in its C terminus, which destabilizes host cytoskeleton by modifying actin. However, whether this effector targets other host factors as well as the function of its N terminus still remains to be determined. Here, we found that SpvB targets clathrin and its adaptor AP-1 (adaptor protein 1) via interactions with its N-terminal domain. Notably, our data suggest that SpvB-clathrin/AP-1 associations disrupt clathrin-mediated endocytosis and protein secretion pathway as well. In addition, knocking down of AP-1 promotes Salmonella intracellular survival and proliferation in host cells.